{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

prodquotrules - 2 6t 3 u= v= u’= v’= 9 f(x =(x 1(x 2 3...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Product rule: u’v+v’u Quotient Rule: (u’v-v’u)/v 2 1. f(x) = (3x - 2) /x u= v= u’= v’= 2. f(x) = x (2x + 1). u= v= u’= v’= 3. f(x) = (x 2 - 2) /(2x). u= v= u’= v’= 4. f(y) = (y + 1) /y 2 u= v= u’= v’= 5. f(x) = (2x + 5) 2 u= v= u’= v’= 6. f(x) = x 2 /(x - 1). u= v= u’= v’= 7. f(z) = z 2 /(2z - 7). u= v= u’= v’=
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Product rule: u’v+v’u Quotient Rule: (u’v-v’u)/v 2 8. y = -2t
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 2 + 6t - 3 u= v= u’= v’= 9. f(x) = (x + 1) (x 2- 3). u= v= u’= v’= 10. f(x) = (2x + 5) /(2x) u= v= u’= v’= 11. f(y) = (3y 2- y) (2 - y). u= v= u’= v’= 12. f(t) = (t 3- 3t) 2 u= v= u’= v’= 13. f(x) = x /(2x + 1). u= v= u’= v’= 14. take the derivative using the limit f(x) = 3x 2 + 4...
View Full Document

{[ snackBarMessage ]}